Ripley's Believe It or Not! : SHATTER YOUR SENSES! - Tibballs, Geoff; Sieck, Sabrina (London : Ripley Publishing, 2017)
A completely new assortment of strange-but-true facts and amazing stories! From the elephant who can play baseball, to the flowers that bloomed in space, to the weasel found inside the world's biggest computer, Ripley's compendium of hair-raising oddities will delight and fascinate the whole family.
Includes index
Keywords: Curiosities and wonders -- Juvenile literature; Juvenile works; Juvenile literature